Annual Plan 1983-84 Government of India Planning Commission - Planning Commission (Planning Commission, 1983)
The Annual Plan for 1983-84, which is the fourth year of the Sixth Five Year Plan, has been formulated in the light of the objectives, policies and programme thrusts indicated in the Sixth Plan and the performance of the economy in the earlier three years. Particular emphasis has been laid on the revised 20-Point Programme, which forms an integral part of the Sixth Plan and focuses attention on some of the most important social and economic programmes aimed at ameliorating the living conditions of weaker sections of the community along with an all round improvement in productivity.
Government of India Planning Commission